Contributions of Numerical Methods Understanding, ChatGPT Use, and AI Learning Attitudes to MATLAB Skills - Syaharuddin (Journal of Education Technology, 2025)
Students continue to experience difficulties in operating computational software such as MATLAB, despite its critical role in solving numerical problems in science and engineering. Amid the rapid integration of artificial intelligence in higher education, there is still limited empirical evidence explaining how conceptual understanding, the use of AI tools, and students’ attitudes toward AI-based learning contribute to their technical skills. This study aims to analyze the contributions of numerical methods conceptual understanding, the use of ChatGPT, and attitudes toward AI-based learning to students’ ability to operate MATLAB. The study employed a quantitative approach with a correlational research design. The participants consisted of 45 students selected through purposive sampling. Data were collected using Likert-scale questionnaires and analyzed using descriptive statistics and multiple linear regression with the assistance of JASP software. The results indicate that conceptual understanding of numerical methods and positive attitudes toward AI-based learning have a significant positive effect on students’ MATLAB operational skills, with significance values of p < 0.001 and p = 0.024, respectively. In contrast, the use of ChatGPT did not show a significant effect (p = 0.914). The regression model yielded a coefficient of determination of 0.782, indicating that 78.2% of the variance in students’ MATLAB skills is explained by the three independent variables. This study concludes that mastery of numerical concepts and positive attitudes toward AI are the primary factors in improving MATLAB skills, while ChatGPT functions as a complementary learning tool rather than a direct determinant of technical competence.